DETERMINING FACTORS OF TEACHER-STUDENT RELATIONSHIPS AMONG SPECIAL ASSISTANT TEACHERS IN INCLUSIVE SCHOOLS: A SCOPING REVIEW - Laili, Nurfi; Nawangsari, Nur Ainy Fardana (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This scoping review aims to examine the relationship between teachers and special assistant teachers (GPK) in inclusive schools, focusing on the factors that influence this relationship to foster a positive learning environment for students with special needs. Method: A systematic search was conducted using keywords such as co-assistant teacher, teacher-student relationship, and inclusive education across electronic databases including Scopus, Proquest, Science Direct, and Taylor & Francis. Using the PRISMA flow diagram (2020) and new.rayyan.ai software, 324 articles were identified, with 10 meeting the inclusion and exclusion criteria for full-text analysis. Results: The review revealed internal and external determinant factors influencing the relationship between teachers and special assistant teachers. Internal factors included teacher self-efficacy, attitudes towards inclusive education, communication styles, and willingness to understand students' special needs. External factors involved cultural and socioeconomic influences, work experience, emotional support, and professional development. Novelty: This study provides a comprehensive overview of the critical factors affecting teacher-GPK relationships, offering valuable insights for enhancing inclusive education practices and improving student outcomes in inclusive settings.